THE CLIMATE OF THE ORGANIZATION FACES THE WORK OF CERTIFIED TEACHERS IN SMAN 1 CENTRAL LAMPUNG - Setya N, Evi Amalia (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The purpose of this research is to find out the impact of the organizational climate on the performance of certified teachers at the Highest State High School. This research is a kind of survey survey survey using quantitative methods. This study involved 182 people, with samples of 119 people. The data collection tool in this study is a method of questionnaire data analysis using simple regression analysis, continued through qualitative descriptions, to get a clearer picture. The results of the research showed that the organizational climate influenced the performance of certified teachers in the State High School at 68.5% and was moderate. Based on the findings, this study draws conclusions to improve the performance of certified teachers, then should improve the organizational climate. The better the organizational culture, the greater the likelihood that a certified teacher's performance will be better and more optimal.